Cross-sectional study of sexual behaviour and knowledge about HIV among urban, rural, and minority residents in Viet Nam - Bui Thang D.; Pham Chi K.; Pham Thang H.; Hoang Long T.; Nguyen Thich V.; Vu Thang Q.; Detels Roger (The World Health Organization, 2001)
OBJECTIVE: A cross-sectional survey was conducted in three districts of Quang Ninh province, Viet Nam, to find out what proportion of the people who lived there engaged in behaviour that put them at risk of becoming infected with HIV, and to measure their knowledge about HIV infection and AIDS. METHODS: The survey was conducted in a rural district, Yen Hung; a mountainous district inhabited primarily by ethnic minority groups, Binh Lieu; and an urban district, Ha Long. Participants aged 15-45 years were randomly selected from the general population to be interviewed. FINDINGS: A total of 630 people from 707 households were interviewed; 8% were not home despite repeated visits and 3% refused to participate. The prevalence of premarital intercourse ranged from 9% to 16% among married men and 4% to 7% among married women. Among single men the proportion who had ever had intercourse ranged from 6% to 16%. Fewer than 3% reported having ever had sex with a sex worker. The median number of extramarital sex partners was 1. Knowledge about HIV/AIDS was high in the urban and rural areas but low in the mountainous area. Being male and being 20-29 years old were associated with having multiple sex partners. CONCLUSION: The low prevalence of individuals reporting that they had had intercourse with sex workers and partners other than their spouse may explain the low rates of HIV infection among the heterosexual population; these rates are in contrast to the high rates of HIV infection found among injecting drug users. The association between having extramarital partners and being a younger man suggests that the tendency to have more sexual partners may increase in the future. If this happens, the potential for HIV to be spread through heterosexual sex will increase.